Development of extruded Mg-6Er-3Y-1.5Zn-0.4Mn (wt.%) alloy with high strength at elevated temperature. Issue 10 (October 2019) - Zhang, Mingquan; Feng, Yan; Zhang, Jinghuai; Liu, Shujuan; Yang, Qiang; Liu, Zhuang; Li, Rongguang; Meng, Jian; Wu, Ruizhi
Abstract: A new Mg-6Er-3Y-1.5Zn-0.4 Mn (wt.%) alloy with high strength at high temperature was designed and extruded at 350 °C. The as-extruded alloy exhibits ultimate tensile strength of 301 MPa, yield strength (along ED) of 274 MPa and thermal conductivity of 73 W/m⋅K at 300 °C. Such outstanding high-temperature strength is mainly attributed to the formation of nano-spaced solute-segregated basal plane stacking faults (SFs) with a large aspect ratio throughout the entire Mg matrix, fine dynamically recrystallized (DRXed) grains of 1–2 μm and strongly textured un-DRXed grains with numerous sub-structures. Microstructural examination unveils that long period stacking ordered (LPSO) phases are formed in Mg matrix of the as-cast alloy when rational design of alloy composition was employed, i.e. (Er + Y): Zn = 3: 1 and Er: Y = 1: 1 (at.%). It is worth mentioning that it is the first report regarding the formation of nano-spaced basal plane SFs throughout both DRXed and un-DRXed grains in as-extruded alloy with well-designed compositions and processing parameters. The results provide new opportunities to the development of deformed Mg alloys with satisfactory mechanical performance for high-temperature services.